Designing for Reuse in an Industrial Internet of Things Monitoring Application - McGee, Ethan T.; Krugh, Matthew; McGregor, John D.; Mears, Laine (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2017)
The Internet of Things (IoT) continues to experience rapid growth, and its influence is extending into previously unreached domains. However, some of these new domains impose specific limitations that complicate the design and implementation of IoT systems. Examples of such limitations are the exclusion of specific protocols, restrictions on the types of data that can be collected, requirements about what information can be transmitted to the public and controls around how that communication occurs. Capturing, representing and designing for these limitations as well as reuse is essential for the quick and successful deployment of such projects. In this paper, we present a case study of an IoT human in the loop monitoring system built for use within an industrial setting. We report our experiences with both designing the first deployment of the system as well as designing variation points into the software architecture to account for future iterations and deployment into other environments.